Statin‐based endothelial prophylaxis and outcome after allogeneic stem cell transplantation. (11th October 2022) - Pabst, Caroline; Schreck, Nicholas; Benner, Axel; Hegenbart, Ute; Schönland, Stefan; Radujkovic, Aleksandar; Schmitt, Michael; Müller‐Tidow, Carsten; Orsatti, Laura; Dreger, Peter; Luft, Thomas
Abstract: Background: Allogeneic haematopoietic stem cell transplantation (alloSCT) often remains the only curative therapy for hematologic malignancies. Although the management of transplant‐associated adverse events considerably improved over the last decades, nonrelapse mortality (NRM) remains a challenge, and endothelial dysfunction was identified as a major contributor to NRM. Methods: Statin‐based endothelial prophylaxis (SEP) has been implemented in the standard of care in our transplant centre to reduce NRM caused by endothelial injury. Here, we retrospectively analysed the impact of SEP on clinical outcome in a cohort of 347 alloSCT patients. Results: SEP ( n  = 209) was associated with significantly reduced NRM (hazard ratio 0.61, 95% CI 0.38–0.96) and better overall survival (OS) after acute graft‐versus‐host disease (HR 0.59, 95% CI 0.37–0.93). Subgroup analyses showed that the NRM benefit was mainly found in patients with an intermediate endothelial activation and stress index (EASIX), while relapse risk was not affected. On day 100 post‐alloSCT, patients receiving SEP had significantly higher levels of the rate‐limiting enzyme of tryptophan metabolism, indoleamine 2, 3‐dioxygenase (IDO), higher kynurenine to tryptophan ratios as a proxy of IDO activity and tended to have lower levels of the endothelial injury marker ST2 ( p  = .055). No significant differences in interferon‐gamma or IL18 levels were observed. These biomarker signatures suggest that the beneficial effects of SEP might be mediated by both endothelial protection and immunomodulation. Conclusions: Together, these data suggest that SEP improves NRM and OS post‐alloSCT in particular in patients with intermediate endothelial risk and provide first mechanistic clues about its potential mode of action. Abstract : Statin‐based endothelial prophylaxis (SEP) has been implemented to reduce nonrelapse mortality (NRM) after allogeneic stem cell transplantation (alloSCT). The impact of SEP on 347 alloSCT patients was retrospectively analysed. SEP improved NRM and overall survival post‐alloSCT in particular in patients with intermediate endothelial activation and stress index (EASIX). On day 100 post‐alloSCT, patients receiving SEP had higher levels of the tryptophan metabolizing enzyme indoleamine 2, 3‐dioxygenase (IDO) and a higher kynurenine to tryptophan ratio, a surrogate of IDO activity.